Development of Learning Material using Gamification for Students with Autism Spectrum Disorder (Program Studi Pendidikan Teknologi Infromasi UMK, 2024)
The basic need for students with an autism spectrum disorder in lectures is repetition in their learning activities. The development of gamification for learning material can accommodate these needs. Information System Department, Universitas Komputer Indonesia, has developed multimedia-based learning material with the concept of gamification for them in two courses as prototypes. Data for the needs for developing learning material was carried out through forum group discussions with experts in the education field for students with special needs. When data is collected from stakeholders, then analyzed with the Strength, Weakness, Opportunity, and Threat model to get a description of the internal and external environment in their learning process. After that, the design, development, and testing (using the black box method and user acceptance testing) of the multimedia application are presented. The result is an application as a prototype which is packaged in a gamification concept to provide interactive audiovisual through the provision of theoretical and practical material video and evaluation by the completion of a mission in a game. The goal is to efficiently deliver material in the learning process for them. The impact of the prototype can be able to improve the quality of the learning experience of students with an autism spectrum disorder.